Development of Alumina-Titania Composite Layers on Stainless Steel through the Detonation Spray Method and Investigation of Salt Spray Corrosion Behavior along with Surface Examination - A. Surya; R. Prakash; P. Senthil Kumar; G. Bharath Balji (International Journal of Chemical Engineering)
Almost every metal and alloy corrodes when used in high-temperature applications. To combat this problem, ceramic coatings on the metals can be deposited for better thermal and corrosion behavior. The present study applies an alumina-titania (Al2O3-TiO2) ceramic coating to the stainless steel (SS) surface using a detonation spray process. The surface of the coated SS is probed by optical microscopy (OM), scanning electron microscopy (SEM), and X-ray diffraction (XRD). The clear differences between coated and uncoated SS have been observed based on the SEM images. The XRD pattern indicates that the Al2O3-TiO2 coating on SS has been successfully deposited. The hardness of coated and uncoated SS surfaces is determined by using the Micro Vickers hardness tester, which claims that the hardness of the SS surface has decreased after coating. Salt spray tests were used to examine the corrosion behavior of coated and uncoated SS after 12 and 24 hours. After 12 hours, no corrosion was observed on the SS. After 24 hours, however, significant corrosion of uncoated SS is observed, and the coated SS shows negligible corrosion. Based on the study, it is claimed that an Al2O3-TiO2 coating on SS has improved its corrosion behavior significantly.